2019
DOI: 10.1002/anie.201906203
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated Lysosomal Escape of a Monofunctional PtII Complex Pt‐BDPA for Nucleus Access

Abstract: A photosensitizing monofunctional Pt complex, Pt‐BDPA, was prepared with a BODIPY chromophore. Apart from its DNA binding ability, this complex displays emission at ca. 578 nm and a singlet oxygen quantum yield of 0.133. Confocal imaging revealed that this complex was sequestered in lysosomes via endocytosis in the dark, preventing its access to the nucleus. Profiting from its photoinduced ROS generation ability, this complex undergoes lysosomal escape to access the nucleus upon photoirradiation. The photoindu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 45 publications
3
64
0
Order By: Relevance
“…[5,16a, 18] These suggest that Pt 2 L has significant photoactivated cytotoxicity,and can improve tumor specificity by selectively irradiating the tumor tissue for tumor treatment. Compared with the reported Pt-BDPAutilizing lysosome sequestration for platinum complex silencing as prodrug, [5] we verified that autolysosomes also can be used for platinum complex sequestration, further opening up new ways for the design of this kind of platinum complexes.S ince autophagy plays av ery important role in tumor and shows environmentally dependent, the real-time…”
Section: Angewandte Chemiesupporting
confidence: 56%
See 3 more Smart Citations
“…[5,16a, 18] These suggest that Pt 2 L has significant photoactivated cytotoxicity,and can improve tumor specificity by selectively irradiating the tumor tissue for tumor treatment. Compared with the reported Pt-BDPAutilizing lysosome sequestration for platinum complex silencing as prodrug, [5] we verified that autolysosomes also can be used for platinum complex sequestration, further opening up new ways for the design of this kind of platinum complexes.S ince autophagy plays av ery important role in tumor and shows environmentally dependent, the real-time…”
Section: Angewandte Chemiesupporting
confidence: 56%
“…As shown in Figure S17, with the increase of irradiation time,t he 2',7'-dichlorofluorescein (DCF) fluorescence increased and Pt 2 L gradually escaped to the nucleus,which suggested that the escape behavior of Pt 2 L was associated with its ROSp roduction and the damage of autolysosomes (Figure 6d), and was consistent with the reported mechanism. [5,18] Fort he first time,w eo bserved an ew transportation path that am atter flux escapes from autolysosomes to nucleus upon light stimulation.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…In order to investigate the possible mechanism of motion effect from nanomotors on cell-to-cell transmission and the intracellular distribution of nanomotors was also studied. We labeled lysosomes (the first barrier faced by nanoparticles after entering cells), [41] nucleus (the main location where…”
Section: Angewandte Chemiementioning
confidence: 99%